Variation Index of the Output Gap (VIOG): A New Way of Testing Potential GDP Estimations (2024)
The potential GDP plays a fundamental role in macroeconomic models used by policymakers to make decisions. Its nature as an unobservable variable has led to the proposition of various estimation techniques based on different assumptions about its generating process. This work proposes a methodology to evaluate the different techniques for estimating potential GDP: the Variation Index of Output Gap (V IOG). Inspired by the statistic mean absolute deviation and the work of Darvas, Vadas, et al. (2003), the V IOG measures the average absolute gap derived from a potential GDP estimation technique. Unlike other methodologies that assess the statistical performance of estimation techniques, the V IOG aims to provide a practical response to the subjective dilemma of potential GDP estimation depending on what policymakers seek: more aggressive economic policies, where a greater output gap is permitted, or more conservative ones, which show a smaller output gap. To illustrate this, an application using the Taylor rule is presented. The results suggest that the differences between using different methodologies to estimate potential GDP can be significant, especially in times of crisis, affecting policymakers’ decisionmaking, implying that depending on the technique used, more or less restrictive economic policy decisions may be taken.